Controlled Acid‐Mediated Regioselective O‐Desilylations for Multifunctionalization of Cyclodextrins. Issue 26 (30th July 2014) - Gu, Jiamin; Chen, Tong; Zhang, Ping; Ling, Chang‐Chun
Abstract: A highly valuable tri‐/tetra‐functionalization method is reported for cyclodextrin (CD) chemistry by taking advantage of the acid‐sensitivity of the O ‐silyl ether group and also the geometry of CD macrocycles. The controlled acid‐mediated O ‐desilylations from the easily accessible per‐3, 6‐ O ‐silylated CD derivatives provide unprecedented regioselectivity to differentiate not only primary O ‐silyl groups from secondary groups, but also O ‐silyl groups of the same type with identical chemical reactivity. This methodology differs from other conventional monofunctionalization methods of natural CDs, which only allow for a direct twofold differentiation of hydroxyl groups in a CD, because the current method permits the synthesis of tri‐ and tetra‐functionalized CDs in a short reaction sequence. Most importantly, the developed method has been found to be applicable to all α‐, β‐, and γ‐CDs and the obtained CD intermediates are versatile. Furthermore, we demonstrate that these processes are practical and can be carried out on multigram scales. Abstract : A controlled acid‐mediated O ‐desilylation method has been developed for cyclodextrin (CD) chemistry using the easily accessible per‐3, 6‐ O ‐silylated CD derivatives as a substrates. This method allows easy access to versatile CD intermediates that can be used for tri‐ or tetra‐functionalizations.